Effect of density on the yield of cassava (Manihot esculentum Crantz) cv. Valencia. - Blanco-Navarro, Moisés; Aguilar-Bustamanete, Víctor; García-López, Jose Rafael; Baldioceda-Manzanares, Chambar (Agronomía Mesoamericana, 2005)
A study of cassava (Manihot esculenta Crantz) cv. Valencia was carried out in June of 2001, in San José de Monte Redondo, Municipality of Masatepe, Masaya Department, Nicaragua. The objective of this test was to assess the effect of 14 286, 15 385, 16 667, 18 182, 20 000 y 22 222 plants per hectare on the components of yield. Spacing was 1m between rows and 0.70, 0.65, 0.60, 0.55, 0.50 y 0.45 m between plants respectively. The experimental design used was a completely randomized blocks design, with four replications. Higher emergency of plants (91.75 %) was obtained with a population of 16,667 plants per hectare (1 x 0.6 m). The highest number of tuberous roots was 5.13 in a density of 14 286 plants per hectare (1 x 0.7). The largest diameter of root (5.20 cm), and the best yield (27.75 t/ha) were obtained with a plant population of 15 385 plants per hectare, when plants were sown at 1 m between rows and 0.65 m between plants. This density caused the formation of the highest quantity of roots for exportation.